2010
DOI: 10.1128/cvi.00398-09
|View full text |Cite
|
Sign up to set email alerts
|

High Seroprevalence of Neutralizing Capacity against Human Metapneumovirus in All Age Groups Studied in Bonn, Germany

Abstract: Human metapneumovirus (hMPV) infections occur frequently despite high rates of perpetual seroprevalence for all age groups. Analyses of ϳ2,000 archived, randomly selected serum samples demonstrated that neutralizing capacities remain high, with a minor decrease for individuals over 69 years of age, leading to the hypothesis that reinfections occur because humoral immune responses play minor roles in the clearance of hMPV infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
1
22
0
1
Order By: Relevance
“…The first HMPV infection appears to take place at 6 months of life, after which infections may occur repeatedly and frequently. The elderly represent the second group of patients that are severely affected by HMPV, and severe HMPV infections in the elderly occur despite high seroprevalence rates and independent of immunosenescence (62,153). Reports on HMPV infections in otherwise healthy adults are relatively rare.…”
Section: Clinical Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The first HMPV infection appears to take place at 6 months of life, after which infections may occur repeatedly and frequently. The elderly represent the second group of patients that are severely affected by HMPV, and severe HMPV infections in the elderly occur despite high seroprevalence rates and independent of immunosenescence (62,153). Reports on HMPV infections in otherwise healthy adults are relatively rare.…”
Section: Clinical Epidemiologymentioning
confidence: 99%
“…Reports on HMPV infections in otherwise healthy adults are relatively rare. Seroprevalence studies indicated that all adults have been infected with HMPV by the age of 25, with very high seroprevalence rates beginning from 5 years of age (68,147,150,153,255,261,262). The nosocomial impact of HMPV is estimated to be as high as that for RSV.…”
Section: Clinical Epidemiologymentioning
confidence: 99%
“…Mice are semipermissive hosts for HMPV, and wild-type B6 mice cannot be reinfected with HMPV, whereas reinfections in humans are common (11,12,41). For this reason, we performed additional experiments in MT mice, which lack mature B cells and can be reinfected with HMPV.…”
Section: Cells (E and F) Expression Of Pd-1 (E) And Other Inhibitorymentioning
confidence: 99%
“…Almost all people acquire seropositivity for hMPV by the age of 10 years, 2 and hMPV is known to infect individuals repeatedly throughout adult life and into old age. [5][6][7][8][9] Although there are no reports of IgG titer differences between patients with hypertension and normotensive controls after individual infections with pathogens, including hMPV, it is possible that hypertension itself may increase the anti-IgG titer in response to repeated hMPV infections in the elderly. In this present cross-sectional study, however, we could not show any time-course data for anti-hMPV-IgG titers in individual subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that reinfection occurs because humoral immune responses have a minor role in the clearance of hMPV. 9 However, the relationship between hMPV infection and the underlying chronic clinical conditions has not been adequately evaluated in elderly subjects. Therefore, the aim of this study was to determine the relationship between the titer of immunoglobulin (Ig) G antibody against hMPV (anti-hMPV-IgG titer) and clinical conditions, including hypertension, in elderly patients in a Japanese LTCF.…”
Section: Introductionmentioning
confidence: 99%